2019
DOI: 10.3389/fmicb.2019.01666
|View full text |Cite
|
Sign up to set email alerts
|

Compositional Shifts of Bacterial Communities Associated With Pyropia yezoensis and Surrounding Seawater Co-occurring With Red Rot Disease

Abstract: Pyropia yezoensis is commercially the most important edible red alga in China, and red rot disease is viewed as one of the major constraints for its cultivation. Microbes within the oomycetic genus Pythium have been reported as the causative agents for this disease; however, little is known about the interactions between the disease and the epiphytic and planktonic bacterial communities. In the present study, bacterial communities associated with uninfected, locally infected, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 83 publications
1
13
0
Order By: Relevance
“…Among this family, OTUs affiliated to Octadecabacter , Silicimonas , Loktanella , and Pseudoruegeria were found positively correlated to the seawater temperature. The Rhodobacteraceae family was already described at the surface of many macroalgae and several taxa within this family were recurrently associated to high temperature conditions [ 27 , 72 – 76 ]. Especially, in the case of D. pulchra , the temperature was associated to the development of several pathogens from the Roseobacter group, such as Nautella italica [ 20 , 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among this family, OTUs affiliated to Octadecabacter , Silicimonas , Loktanella , and Pseudoruegeria were found positively correlated to the seawater temperature. The Rhodobacteraceae family was already described at the surface of many macroalgae and several taxa within this family were recurrently associated to high temperature conditions [ 27 , 72 – 76 ]. Especially, in the case of D. pulchra , the temperature was associated to the development of several pathogens from the Roseobacter group, such as Nautella italica [ 20 , 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…Microbiome Diversity in the microbiota P. umbilicalis -Seasonal variation to the microbial community in laver -Identification of bacterial groups which are expected to contribute to the evolution and/or function of laver [155] P. yezoensis -Seasonal variation and the effects of the yellow spot disease outbreaks to the microbial community in the seawater of laver seedling pools -Identification of disease-associated bacteria [174] Analytical techniques P. umbilicalis -Microbial communities affected by the sampling position of laver and the stabilization techniques applied for the microbiome analysis [171] Influencing factor (Red rot disease) P. yezoensis -Alterations of bacterial community by red dot disease -Close association between health status of algal host (uninfected or infected) and bacterial community [190] Proteome Mechanism of stress-tolerance P. haitanensis -Investigation on the key metabolisms elucidating the mechanisms of resistance to high-temperature [175,176] P. orbicularis -Investigation on the key metabolisms elucidating the mechanisms of resistance to desiccation [177,178]…”
Section: Omics Technology Topic Species Major Findings Referencesmentioning
confidence: 99%
“…For example, an analysis of the epiphytic microbial community of P. haitanensis thalli using the denaturing gradient gel electrophoresis method revealed that the microbial community varied based on growth form, culture time, and environment (Shen et al 2013). Microbial communities on Pyropia yezoensis thalli and in seawater were significantly different when infected with the oomycetic genus Pythium (Yan et al 2019). In addition, industrial cultivation of the conchocelis stage is also an important component of the Pyropia industry.…”
Section: Introductionmentioning
confidence: 99%